Infiltração de água no solo condicionadas pelo uso de plantas de cobertura - Mallmann, Micael Stolben (2017)
The inclusion of cover crops in agricultural production systems has received attention for the ability to improve the multifunctionality of the soil. In order to improve soil structure and soil physical-hydric properties, especially soil water infiltration, the objective of this study was: (a) to evaluate the effect of different species of winter cover crops on soil physical properties and (b) to verify the relationship between punctual methods for the evaluation of water infiltration in the soil and the infiltration of water with natural rainfall on plot scale. For the first study the systems studied were: oat and vetch (AE) consortium, oat and turnip (AN), spontaneous vegetation (VE) and bare soil (SD). Soil samples with undisturbed structure were collected in the layers of 0 - 0,05; 0,05 - 0,1; 0,1 - 0,2 and 0,2 - 0,3 m to measure bulk density (DS), total porosity (Pt), macroporosity (Mac), microporosity (Mic), saturated soil hydraulic conductivity (Ksat) and permeability to air (Ka). Soil aggregation was also evaluated in the layers of 0 - 0.05 and 0.5 - 0.1 m. Soil water infiltration was determined by the concentric double ring method. For the second study, three treatments were used in the first study to determine the rate of stable infiltration of soil water (TIE) by the Cornell infiltrometer, double ring infiltrometer and infiltration in natural rainfall events. The results indicate that after the cultivation of winter cover crops, there are no changes in the physical properties evaluated, but there is evidence of improved water infiltration in the soil and the continuity and pore diameter in the treatments with cover crops. The TIE determined by the Cornell infiltrometer and double ring infiltrometer method is overestimated from 1.8 to 2.2 times that of natural rainfall.